Strategi Supervisi Akademik Kepala Sekolah dalam Mengembangkan Profesionalisme Guru di SMAN 1 Labuapi - Lu'luin Najwa; Hardiansyah (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2025)
This study aims to describe the academic supervision strategies employed by the principal in developing teacher professionalism at SMAN 1 Labuapi. The research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation. The research informants consisted of the principal, teachers, and the vice principal for academic affairs, selected through purposive sampling. Data analysis was conducted using the interactive analysis model developed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that the principal implements various academic supervision strategies, including individual supervision, classical supervision, group supervision, and reflective supervision. These strategies contribute positively to enhancing teacher professionalism, particularly in pedagogical, professional, social, and personal competencies. The challenges encountered in implementing academic supervision include limited time, varying levels of teacher preparedness, and a lack of optimal follow-up after supervision activities. The principal addresses these challenges by involving the school management team, prioritizing supervision based on teacher needs, and recognizing high-performing teachers with awards. This study concludes that well-planned, systematic, and collaborative academic supervision can effectively improve teacher professionalism. It is recommended that principals continue to develop innovative academic supervision models to foster a culture of quality learning in schools.